Drosophila Sas-6, Ana2 and Sas-4 self-organise into macromolecular structures that can be used to probe centriole and centrosome assembly - Gartenmann, Lisa (J Cell Sci, 2020)
Centriole assembly requires a small number of conserved proteins. The precise pathway of centriole assembly has been difficult to study, as the lack of any one of the core assembly proteins [Plk4, Ana2 (the homologue of mammalian STIL), Sas-6, Sas-4 (mammalian CPAP) or Asl (mammalian Cep152)] leads to the absence of centrioles. Here, we use Sas-6 and Ana2 particles (SAPs) as a new model to probe the pathway of centriole and centrosome assembly. SAPs form in Drosophila eggs or embryos when Sas-6 and Ana2 are overexpressed. SAP assembly requires Sas-4, but not Plk4, whereas Asl helps to initiate SAP assembly but is not required for SAP growth. Although not centrioles, SAPs recruit and organise many centriole and centrosome components, nucleate microtubules, organise actin structures and compete with endogenous centrosomes to form mitotic spindle poles. SAPs require Asl to efficiently recruit pericentriolar material (PCM), but Spd-2 (the homologue of mammalian Cep192) can promote some PCM assembly independently of Asl. These observations provide new insights into the pathways of centriole and centrosome assembly.